Elimination of ƞ phase in WC–Co cemented carbides during laser powder bed fusion by powder coating compensation strategy. Issue 3 (24th November 2022) - Wang, Yemin; Zhang, Lei; Yang, Yafeng; Kondoh, Katsuyoshi; Sun, Linbing; Lu, Yanan
Abstract: The formation of ƞ phase induced by the C‐loss for the laser powder bed fusion (LPBF) of WC–Co cemented carbides largely deteriorates the fracture toughness. The current approach of mixing C additive into powder cannot mitigate the ƞ phase formation. This study proposed a new carbon compensation strategy of coating carbon resource on powder surface by fluidized bed chemical vapor deposition to address this issue. C nanoparticles and carbon nanotubes (CNTs) were selectively deposited on WC–Co powder to make uniform C‐ and CNTs‐coated powders by tuning the deposition temperature. Compared with CNTs‐coated powder and C–WC–Co powder mixtures, the C‐coated powder was more effective in impeding the ƞ phase formation because it had higher reactivity and stronger dissolution ability to compensate the C‐loss in the Co–W–C liquid. However, the single‐carbon compensation was not enough to eliminate the ƞ phase due to the extreme nonequilibrium characteristics of LPBF, which required secondary heat treatment. The conventional heat treatment procedure of 1000°C for 3 h eliminated the ƞ phase for the C‐coated powder but failed for the C–WC–12Co powder mixtures. Because of the absence of ƞ phase, the heat‐treated sample made from C‐coated powder exhibited the highest transverse rupture strength.